Phenotype and Molecular Characterizations of 30 Children From China With NR5A1 Mutations - Song, Yanning; Fan, Lijun; Gong, Chunxiu (Frontiers in Pharmacology, 2018)
Background: Patients harboring NR5A1 mutations have a wide spectrum of phenotypes. Objective: To investigate the phenotype of patients with NR5A1 gene mutations from a 30 Chinese patient cohort. Methods: We reported the clinical features of children with NR5A1 gene mutations and compared them between 2 groups of patients with social genders of male (boys group) and female (girls group). Results: Thirty patients with NR5A1 mutations ranging from 2 months to 17 years of age were studied. There were 11 boys and 19 girls who were identified when they visited the hospital. The patients were verified as having testes without a uterus and ovaries by B-mode ultrasound. There was no difference between boys and girls in terms of the Prader stage (p=0.086), but the position of the testes was higher in girls than in boys (p=0.013). The patients’ average height is -0.43 SDS according to the normal boys’ height with SDS (while their average target height was 0.07 SDS). However, there was no such difference between boys and girls (p>0.05). Although the basal LH and post-hCG testosterone (T) levels were not different (p>0.05), but the basal FSH level, LH/FSH ratio, and INHB level were decreased in girls (p=0.002; p=0.001; p=0.006). All of the mothers of the patients reported to have normal pregnancies. We found 24 patients (80%) with de novo mutations in the NR5A1 gene; 5 patients had inherited mutations from their mothers, and one inherited from the father. Only the mothers of patients 16 and 18 showed premature ovarian failure at the time of reporting. Among 26 disease associated mutations, 14 novel mutations that have been reported the first time and p.R87C is the most common Among the other 12 had had been reported，the p.R313C is the most common. Conclusions: Patients with 46, XY NR5A1 mutations presented a wide spectrum of external genitalia characteristics and severe Sertoli cell impairment. The p.R87C and p.R313C mutations appeared to be common (10%) in this group, and 14 new mutations were identified, improving our understanding the genotype phenotype correlations.